Organisation of the murine 5-HT3 receptor gene and assignment tohuman chromosome 11 - Uetz, Peter; Abdelatty, Fawzy; Villarroel, Alfredo; Rappold, Gudrun; Weiß, Birgit; Koenen, Michael (FEBS letters, 1994)
We have isolated the murine gene encoding the 5-HT3 receptor (5-HT3R), a member of the ligand-gated ion channels, that mediates a variety of physiological effects in central and peripheral neurons. DNA sequence analysis of the 5-HT3R gene revealed its organisation in 9 exons distributed over approximately 12 kbp of DNA. Alternative use ofexon 9 splice acceptor sites generated two 5-HT3R variants. The 5-HT3R gene, whose structure is closely related to neuronal and muscle AChRα genes, as demonstrated by four common splice junctions, was localised on human chromosome 11.
Gesehen am 31.03.2021